2022
DOI: 10.3389/fonc.2022.848594
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Neutrophil Extracellular Traps in Colorectal Cancer and Beyond: From Bench to Bedside

Abstract: Neutrophil extracellular traps (NETs), products of neutrophil death when exposed to certain stimuli, were first proposed as a type of response to bacterial infection in infectious diseases. Since then, extensive studies have discovered its involvement in other non-infectious inflammatory diseases including thromboembolism, autoimmune diseases, and cancer. Colorectal cancer (CRC) is one of the most common malignancies in the world. NET formation is closely associated with tumorigenesis, progression, and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…Recently, increasing evidence has shown that neutrophil extracellular traps (NETs) play vital roles in tumor initiation, progression, recurrence, and metastasis ( 27 , 44 ). In particular, NETs may play essential roles in the tumor microenvironment and are crucial to cancer immunotherapy ( 52 , 53 ). Additionally, several prognostic models based on NETs have been shown in various human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence has shown that neutrophil extracellular traps (NETs) play vital roles in tumor initiation, progression, recurrence, and metastasis ( 27 , 44 ). In particular, NETs may play essential roles in the tumor microenvironment and are crucial to cancer immunotherapy ( 52 , 53 ). Additionally, several prognostic models based on NETs have been shown in various human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum may also promote immune evasion by binding the Fap2 protein to the immunosuppressive T-cell immunoglobulin and ITIM domain receptor, which inhibits T-cell activation and induces the death of human natural killer cells[ 131 , 132 ]. In addition, the gut microbiome may influence macrophage polarization and the formation of neutrophil extracellular traps, which may promote tumor metastasis through local invasion, increase vascular permeability, and facilitate immune escape and colonization[ 133 , 134 ].…”
Section: Gut Microbiota and Progression Of Crcmentioning
confidence: 99%
“…Together, the above findings suggest that HSPs as a danger signal may regulate neutrophil polarization. Here, we have reviewed the tumor- promoting role of neutrophils by focusing on N2-type TANs that exploit diverse mechanisms to promote tumor progression, such as secreting inflammatory cytokines and chemokines ( 48 , 49 ), releasing NETs ( 50 ), and epithelial-to-mesenchymal transition (EMT) ( 51 ) ( Table 1 ), which we have discussed in detail in the following subsections.…”
Section: Neutrophils In Cancer Progressionmentioning
confidence: 99%